Nutritional assessment of composite postnatal diets formulated from traditionally fermented cereal blends - Adegbola, Grace Mosunmola; Gabriel-Ajobiewe, Ruth Adefolakemi O.; Gabriel-Ogunniyi, Blessing Mosope; Odeleye, Olawale Peter; Adeleke, Bartholomew Saanu (Edelweiss Applied Science and Technology, 2026)
This study was designed to evaluate the nutritional quality and acceptability of composite postnatal diets formulated from traditionally fermented cereals. The physicochemical properties, proximate, mineral, vitamins, and sensory attributes of the fermented products were assessed. In the fermented samples, the total dissolved solids (TDS) were lower compared to the control, with minimum values of 158, 190, and 181 ppm recorded at 24 hours of fermentation. However, at 120 hours, an increase in TDS values of 317, 336, and 565 ppm was observed. Optimal fermentation temperatures of 27-28°C were recorded at 48 hours. The pH of fermented sample A increased from 3.5 to 4.0. Proximate analysis showed an increase in protein content, with a maximum value of 28.87%. Improvements were also observed in fiber, fat, carbohydrate, and moisture contents. Ash content showed no significant difference between fermented and unfermented samples. Mineral analysis revealed an increase in phosphorus and calcium contents in the fermented samples, whereas potassium and magnesium contents were higher in the unfermented samples. The fermented products also exhibited varied vitamin contents. Sensory evaluation showed that the fermented recipe composed of yellow maize, red sorghum, millet, African-yam beans, turmeric, and alligator pepper scored highest for color and texture. Overall, traditional cereal fermentation improved the nutritional profile, mineral bioavailability, and sensory quality of the composite postnatal diets, supporting their affordable use as nutrient-dense foods for postnatal nutrition.